Typical MRI Features of a Vein of Galen Aneurysmal Malformation. Issue 1 (22nd June 2020) - Vande Berg, Damienne; Pitcher, Richard; Dumitriu, Dana
Teaching Point: Typical imaging features of a vein of Galen aneurysmal malformation are enlarged intracranial arterial feeders to a dilated recipient vein.